Magnetic nano-particles as well as preparation method and application thereof

By using the mixing and melting treatment of specific materials A and B in the preparation process of Sm-Fe-N magnetic powder, combined with rotating cold rollers and nitriding treatment, and adding doped element Ti, high-magnetic performance magnetic nanoparticles with particle size less than 50 nm were successfully prepared, which solved the problem of particle size limitation in the prior art and significantly improved the coercive force and residual magnetic properties of the material.

CN119541982APending Publication Date: 2025-02-28HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311086643.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to prepare Sm-Fe-N magnetic powder with a particle size below 50 nm, which limits the coercive force and residual magnetic properties of the material.

Method used

The mixture and melting process of H3BO3, CaCl2, NaCl, KCl and other materials A and Sm2O3, Fe2O3 and TM oxide are used to make a sheet-like amorphous medium by rotating the cold roller, and doping element Ti is added to the nitriding treatment to prevent excessive growth of grains and form magnetic nanoparticles with high magnetic properties.

Benefits of technology

Magnetic nanoparticles with particle size less than 50nm were successfully prepared, with the magnetic powder particle size below 40nm, Ms up to 151.5emu/g, and Hcj up to 25.3kOe, significantly improving the coercive force and residual magnetic properties of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides magnetic nanoparticles and a preparation method and application thereof.The chemical formula of the magnetic nanoparticles is Sm alpha Fe gamma TM beta N epsilon, TM comprises titanium, alpha is larger than or equal to 2 and smaller than or equal to 4, gamma is larger than or equal to 16.5 and smaller than or equal to 17.5, beta is larger than or equal to 0.05 and smaller than or equal to 0.5, epsilon is larger than or equal to 3.1 and smaller than or equal to 3.5, and the particle size of the magnetic nanoparticles ranges from 20 nm to 50 nm. And the method is more suitable for miniaturization and light-weight development of magnetic components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials and relates to magnetic nanoparticles and a preparation method and application thereof. Background Art

[0002] At present, information products such as computers are developing towards miniaturization and high performance. Permanent magnet theory shows that the larger the maximum magnetic energy product of the permanent magnet material used, the less permanent magnet material is needed, so the preparation of permanent magnet materials with high magnetic energy product is very important for the miniaturization and lightness of devices. Among various permanent magnet materials today, rare earth permanent magnet materials have attracted widespread attention due to their excellent permanent magnetic properties.

[0003] Rare earth permanent magnet materials are a type of high-performance permanent magnet materials formed by rare earth elements R (Sm, Nd, Pr, etc.) and transition metals TM (Fe, Co, etc.). So far, this type of material includes the first generation RCo5 series, the second generation R2Co17 series and the third generation NdFeB series rare earth permanent magnet materials. Sm-Fe-N rare earth permanent magnets have a higher Curie temperature (Tc=750K), a higher anisotropy field (HA=12MA / m) and a similar saturation magnetization (Bs=1.56T) than NdFeB series rare earth permanent magnet materials, and are likely to become a new generation of rare earth permanent magnet materials.

[0004] Since the 1990s, researchers from all over the world have tried to synthesize Sm-Fe-N permanent magnet materials using different methods. CN 1093311C discloses a method of preparing Sm-Fe-N series alloy powders by reduction diffusion and using the powders to prepare bonded magnets.

[0005] CN 100513015C discloses a Sm-Fe-N series alloy powder with high sphericity and a preparation method thereof, which further improves the coercive force of the material.

[0006] According to relevant magnetic theories, when the grains of magnetic materials are close to the single domain size, the coercivity of the material will be greatly improved. In particular, when the grains of the material are refined to the nanoscale (below 100nm), there will be exchange coupling between the grains, thereby greatly improving the remanence of the material.

[0007] The above methods can all prepare Sm-Fe-N magnetic powder with excellent performance, but due to process limitations, only magnetic powder with a particle size of more than 500 nm can be prepared. Summary of the invention

[0008] The object of the present invention is to provide a magnetic nanoparticle and a preparation method and application thereof. The magnetic nanoparticle of the present invention has a small particle size (below 50nm) and high magnetic properties, and is more suitable for the development of miniaturization and lightweight of magnetic components.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a magnetic nanoparticle, wherein the chemical formula of the magnetic nanoparticle is Sm α Fe γ TM β N ε , wherein TM includes titanium element, 2≤α≤4, 16.5≤γ≤17.5, 0.05≤β≤0.5, 3.1≤ε≤3.5, and the particle size of the magnetic nanoparticles is 20 to 50 nm, for example: 20 nm, 25 nm, 30 nm, 40 nm or 50 nm, etc.

[0011] The magnetic nanoparticles described in the present invention are nanoscale magnetic powder particles (particle size is within 50nm). The magnetic nanoparticles contain both sufficient magnetic main phase and doping elements pinned at the grain boundaries to prevent abnormal growth of grains during the crystallization / nitridation process, thereby obtaining high magnetic properties while forming nanostructured particles.

[0012] Preferably, the TM further comprises any one of cobalt, vanadium, chromium, manganese or nickel, or a combination of at least two of them.

[0013] Preferably, α, γ, β and ε satisfy the following relationship:

[0014] 5≤(γ+β) / α≤8.5, for example: 5, 6, 7, 8 or 8.5, etc.;

[0015] 0.05≤β≤0.5, for example: 0.05, 0.08, 0.1, 0.32 or 0.5, etc.;

[0016] 1.35≤ε / α≤1.8, for example: 1.35, 1.4, 1.5, 1.6 or 1.8, etc.

[0017] In a second aspect, the present invention provides a method for preparing the magnetic nanoparticles as described in the first aspect, the preparation method comprising the following steps:

[0018] (1) H3BO3, CaCl2, NaCl and KCl are mixed to obtain material A, Sm2O3, iron oxide and TM oxide are mixed, ground and then reduced to obtain material B;

[0019] (2) mixing material A and material B and then melting them to obtain a molten liquid, and flowing the molten liquid onto a rotating cold roller to obtain a flaky amorphous medium;

[0020] (3) The flaky amorphous medium is crushed and then crystallized, and then nitrided to obtain nitride, which is then washed and passivated to obtain the magnetic nanoparticles.

[0021] In the preparation method described in the present invention, the TM element (which must contain Ti) uses its pinning effect at the grain boundary during the crystallization and nitridation processes to prevent excessive particle growth. The addition of Ti needs to comprehensively consider its influence on the microstructure of the material in different process flows (reduction, amorphization, crystallization), and also needs to consider the influence of its addition on the magnetic properties of the material.

[0022] Preferably, based on the mass of the material A being 100%, the mass fraction of the H3BO3 is 40-75%, for example, 40%, 45%, 50%, 60% or 75%.

[0023] Preferably, based on the mass of the material A being 100%, the mass fraction of the CaCl2 is 15-20%, for example, 15%, 16%, 18%, 19% or 20%.

[0024] Preferably, based on the mass of the material A being 100%, the mass fraction of the NaCl is 5-20%, for example, 5%, 8%, 10%, 15% or 20%.

[0025] Preferably, based on the mass of the material A being 100%, the mass fraction of KCl is 5-20%, for example, 5%, 8%, 10%, 15% or 20%.

[0026] The material A of the present invention has multiple functions. First, it acts as a flux to reduce the melting point of the mixture after reduction. Second, it adjusts the viscosity of the molten mixture so that the molten mixed liquid can be easily spread on the roller quickly, thereby controlling the thickness of the flaky amorphous medium and optimizing the microstructure of the medium. Third, in the crystallization process of the amorphous medium, it plays a role in isolating Sm α Fe γ TM β The main phase controls the growth of particles; fourthly, when washed in water, since material A is composed of H3BO3, CaCl2, NaCl, and KCl, it is easily soluble in water, thus playing a role in disintegrating the crystallization-nitridation product. After the crystallization-nitridation product is dissolved and washed with water (acid), H3BO3, CaCl2, NaCl, KCl and the reduction product CaO are separated, leaving only Sm-Fe-TM-N nanoparticles that are insoluble in water (acid).

[0027] Preferably, the grinding in step (1) comprises ball milling.

[0028] Preferably, the reduction treatment includes hydrogen reduction and calcium reduction.

[0029] Preferably, the temperature of the hydrogen reduction is 800-900°C, for example, 800°C, 820°C, 850°C, 880°C or 900°C.

[0030] Preferably, the temperature of calcium reduction is 950-1050°C, for example, 950°C, 980°C, 1000°C, 1020°C or 1050°C.

[0031] Preferably, the mass ratio of material A to material B in step (2) is (20-50):(50-80), for example: 20:80, 30:70, 40:60 or 50:50, etc.

[0032] Preferably, the temperature of the melt treatment is 1300-1500°C, for example, 1300°C, 1350°C, 1400°C, 1450°C or 1500°C.

[0033] Preferably, the outflow speed is 4 to 6 g / s, for example, 4 g / s, 4.5 g / s, 5 g / s, 5.5 g / s or 6 g / s.

[0034] Preferably, the rotating cold roller is made of copper alloy and / or molybdenum alloy.

[0035] Preferably, the rotating speed of the rotating cold roller is 20-30 m / s, for example, 20 m / s, 22 m / s, 25 m / s, 28 m / s or 30 m / s.

[0036] Preferably, the roughness of the rotating cold roller is 0.05-0.2 μm, for example, 0.05 μm, 0.08 μm, 0.1 μm, 0.15 μm or 0.2 μm.

[0037] Preferably, the atmosphere of the crystallization treatment in step (3) includes argon.

[0038] Preferably, the temperature of the crystallization treatment is 580-620°C, for example, 580°C, 590°C, 600°C, 610°C or 620°C.

[0039] Preferably, the crystallization treatment time is 4 to 6 hours, for example: 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0040] Preferably, the atmosphere of the nitridation treatment includes ammonia.

[0041] Preferably, the temperature of the nitridation treatment is 430-480°C, for example, 430°C, 440°C, 450°C, 460°C or 480°C.

[0042] Preferably, the nitriding treatment time is 5 to 7 hours, for example: 5 hours, 5.5 hours, 6 hours, 6.5 hours or 7 hours.

[0043] Preferably, the washing treatment includes water washing, acid washing and alcohol washing.

[0044] Preferably, the washing is followed by a drying process.

[0045] Preferably, the atmosphere of the passivation treatment includes a nitrogen-oxygen mixed gas with an oxygen content of 0.5%.

[0046] Preferably, the passivation treatment time is 40 to 60 hours, for example, 40 hours, 45 hours, 50 hours, 55 hours or 60 hours.

[0047] In a third aspect, the present invention provides a magnetic component, wherein the magnetic component comprises the magnetic nanoparticles as described in the first aspect.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The magnetic nanoparticles described in the present invention are nanoscale magnetic powder particles (particle size is within 50 nm). The magnetic nanoparticles contain both sufficient magnetic main phase and doping elements pinned at the grain boundaries to prevent abnormal growth of grains during the crystallization / nitridation process, thereby obtaining high magnetic properties while forming nanostructured particles.

[0050] (2) The magnetic nanoparticles of the present invention have a particle size of less than 40 nm, an Ms of more than 151.5 emu / g, and a Hcj of more than 25.3 kOe. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Example 1

[0053] This embodiment provides a magnetic nanoparticle, and the preparation method of the magnetic nanoparticle is as follows:

[0054] (1) Weigh H3BO3, CaCl2, NaCl, and KCl in the following weight ratios: H3BO3 40%, CaCl2 20%, NaCl 20%, and KCl 20%, and mix to obtain material A; weigh Sm2O3, Fe2O3, and Ti2O3 in proportion so that the ratio of each element in the mixture satisfies the chemical formula Sm α Fe γ TMβ ; wherein α=2.1, γ=16.9, β=0.1, and the mixture is put into a ball mill for ball milling, wherein the grinding balls are steel balls, and the ball milling medium is water, wherein the mass ratio of balls, materials, and water is 10:1:1.5, and the ball milling time is 4 hours, and the uniformly mixed slurry is heated at 100°C to evaporate the water to become a dry powder, and then reduced with hydrogen at 850°C until all the transition oxides in the mixture are reduced, and the powder after hydrogen reduction is mixed with metal Ca, and then heated to 1000°C under the protection of argon gas for Ca reduction, until all the Sm2O3 in the mixture is reduced, to obtain material B;

[0055] (2) Material A and material B are mixed in a mass ratio of 30:70, and after being uniformly mixed, they are placed in a crucible and heated to 1400° C. in vacuum to completely melt them, and then the solution is stirred while heating the outflow port provided at the bottom of the crucible, so that the solution flows out in a columnar shape at a speed of about 5 g / s onto a high-speed rotating water-cooled roller to obtain a flaky amorphous medium, wherein the roller speed is 25 m / s and the roller surface roughness is controlled to be 0.05 μm;

[0056] (3) The amorphous medium is crushed, and then heated to 600°C (crystallization temperature) under argon protection, and kept warm for 5 hours for crystallization treatment; then the temperature is lowered to 450°C, the argon is evacuated and ammonia is filled in for nitridation treatment, the treatment time is 6 hours, and then cooled to room temperature to obtain nitride, the nitrided product is placed in deionized water, stirred and washed, and H3BO3, CaCl2, NaCl, KCl and other substances as well as CaO products generated during the Ca reduction process are washed away. In order to completely remove CaO, a small amount of hydrochloric acid or acetic acid can also be added to the solution, and then deionized water is used to wash 1-2 times, and the washed product is further washed with alcohol, and the alcohol is filtered and vacuum dried at a temperature of 60°C. A nitrogen-oxygen mixed gas with an oxygen content of 0.5% is passed through the powder for 48 hours at room temperature to obtain the magnetic nanoparticles. According to nitrogen content analysis, the formed compound Sm α Fe γ TM β N ε In, ε=3.20, (γ+β) / α=8.10, ε / α=1.52.

[0057] Example 2

[0058] This embodiment provides a magnetic nanoparticle, and the preparation method of the magnetic nanoparticle is as follows:

[0059] (1) H3BO3, CaCl2, NaCl, and KCl are weighed in the following weight ratios: H3BO3 75%, CaCl2 15%, NaCl 5%, and KCl 5%, and mixed to obtain material A; Sm2O3, Fe2O3, Ti2O3, and CoO (TM includes Ti and Co, Ti:Co=5:1) are weighed in proportion so that the ratio of each element in the mixture satisfies the chemical formula Sm α Fe γ TM β ; wherein α=2.1, γ=16.9, β=0.1, the mixture is put into a ball mill for ball milling, the grinding balls are steel balls, the ball milling medium is water, the mass ratio of balls, material and water is 10:1:1.5, the ball milling time is 4 hours, the uniformly mixed slurry is heated at 100°C to evaporate the water to become a dry powder, and is reduced with hydrogen at 800°C until the transition oxides in the mixture are completely reduced, the hydrogen-reduced powder is mixed with metal Ca, and then heated to 950°C under the protection of argon gas for Ca reduction until the Sm2O3 in the mixture is completely reduced to obtain material B;

[0060] (2) Material A and material B are mixed in a mass ratio of 20:80, and after being uniformly mixed, they are placed in a crucible and heated to 1300° C. in vacuum to completely melt them, and then the solution is stirred while heating the outflow port provided at the bottom of the crucible, so that the solution flows out in a columnar shape at a speed of about 4 g / s onto a high-speed rotating water-cooled roller to obtain a flaky amorphous medium, wherein the roller speed is 20 m / s and the roller surface roughness is controlled to be 0.1 μm;

[0061] (3) The amorphous medium is crushed, and then heated to 580°C (crystallization temperature) under argon protection, and kept warm for 6 hours for crystallization treatment; then the temperature is lowered to 430°C, the argon is evacuated and ammonia is filled in for nitridation treatment, the treatment time is 7 hours, and then cooled to room temperature to obtain nitride, the nitrided product is placed in deionized water, stirred and washed, and H3BO3, CaCl2, NaCl, KCl and other substances as well as CaO products generated during the Ca reduction process are washed away. In order to completely remove CaO, a small amount of hydrochloric acid or acetic acid can also be added to the solution, and then deionized water is used to wash 1-2 times, and the washed product is further washed with alcohol, and the alcohol is filtered and vacuum dried at a temperature of 60°C. A nitrogen-oxygen mixed gas with an oxygen content of 0.5% is passed through the powder for 40 hours at room temperature to obtain the magnetic nanoparticles. According to nitrogen content analysis, the formed compound Sm α Fe γ TM β N ε In, ε=3.15, (γ+β) / α=8.10, ε / α=1.5.

[0062] Example 3

[0063] This embodiment provides a magnetic nanoparticle, and the preparation method of the magnetic nanoparticle is as follows:

[0064] (1) H3BO3, CaCl2, NaCl, and KCl are weighed in the following weight ratios: H3BO3 55%, CaCl2 15%, NaCl 15%, and KCl 15%, and mixed to obtain material A; Sm2O3, Fe2O3, Ti2O3, and V2O5 (TM includes Ti and V, Ti:V=4:1) are weighed in proportion so that the ratio of each element in the mixture satisfies the chemical formula Sm α Fe γ TM β ; wherein α=2.1, γ=16.9, β=0.1, the mixture is put into a ball mill for ball milling, the grinding balls are steel balls, the ball milling medium is water, the mass ratio of balls, material and water is 10:1:1.5, the ball milling time is 4 hours, the uniformly mixed slurry is heated at 100°C to evaporate the water to become a dry powder, and is reduced with hydrogen at 900°C until the transition oxides in the mixture are completely reduced, the hydrogen-reduced powder is mixed with metal Ca, and then heated to 1050°C under the protection of argon gas for Ca reduction until the Sm2O3 in the mixture is completely reduced to obtain material B;

[0065] (2) Material A and material B are mixed in a mass ratio of 50:50, and after being uniformly mixed, they are placed in a crucible and heated to 1500° C. in vacuum to completely melt them, and then the solution is stirred while heating the outflow port provided at the bottom of the crucible, so that the solution flows out in a columnar shape at a speed of about 6 g / s onto a high-speed rotating water-cooled roller to obtain a flaky amorphous medium, wherein the roller speed is 30 m / s and the roller surface roughness is controlled to be 0.2 μm;

[0066] (3) The amorphous medium is crushed, and then heated to 620°C (crystallization temperature) under argon protection, and kept warm for 4 hours for crystallization treatment; then the temperature is lowered to 480°C, the argon is evacuated and ammonia is filled in for nitridation treatment, the treatment time is 5 hours, and then cooled to room temperature to obtain nitride, the nitrided product is placed in deionized water, stirred and washed to wash away H3BO3, CaCl2, NaCl, KCl and other substances as well as CaO products generated during the Ca reduction process. In order to completely remove CaO, a small amount of hydrochloric acid or acetic acid can also be added to the solution, and then deionized water is used to wash 1-2 times, and the washed product is further washed with alcohol, and the alcohol is filtered and vacuum dried at 60°C. A nitrogen-oxygen mixed gas with an oxygen content of 0.5% is introduced into the powder for 60 hours for passivation treatment at room temperature to obtain the magnetic nanoparticles. According to nitrogen content analysis, the formed compound Sm α Feγ TM β N ε In, ε=3.15, (γ+β) / α=8.10, ε / α=1.5.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 1 is that α=3.4, γ=16.9, β=0.1, and other conditions and parameters are exactly the same as those in embodiment 1. The nitrogen content of the formed compound Sm α Fe γ TM β N ε In, ε=4.8, (γ+β) / α=5, ε / α=1.41.

[0069] Example 5

[0070] The difference between this embodiment and embodiment 1 is that α=2.1, γ=17.5, β=0.5, and other conditions and parameters are exactly the same as those in embodiment 1. The nitrogen content of the formed compound Sm α Fe γ TM β N ε In, ε=3.05, (γ+β) / α=8.57, ε / α=1.45.

[0071] Example 6

[0072] The only difference between this embodiment and embodiment 1 is that the composition of material A is 30% H3BO3, 25% CaCl2, 25% NaCl, and 20% KCl, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0073] Example 7

[0074] The only difference between this embodiment and embodiment 1 is that the composition of material A is H3BO3 80%, CaCl2 10%, NaCl5%, KCl 5%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0075] Example 8

[0076] The only difference between this embodiment and embodiment 1 is that the surface roughness of the roller in step (2) is 0.03%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0077] Example 9

[0078] The only difference between this embodiment and embodiment 1 is that the surface roughness of the roller in step (2) is 0.3%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0079] Comparative Example 1

[0080] Weigh Sm2O3, Fe2O3, Ti2O3 and V2O5 (TM includes Ti and V, Ti:V = 4:1) in proportion so that the ratio of each element in the mixture satisfies the chemical formula Sm α Fe γ TM β ; wherein α=2.1, γ=16.9, β=0.1, the mixture is put into a ball mill for ball milling, the grinding balls are steel balls, the ball milling medium is water, the mass ratio of balls, material and water is 10:1:1.5, the ball milling time is 4 hours, the uniformly mixed slurry is heated at 100°C to evaporate the water to become a dry powder, and is reduced with hydrogen at 900°C until the transition oxides in the mixture are completely reduced, the hydrogen-reduced powder is mixed with metal Ca, and then heated to 1050°C under the protection of argon gas for Ca reduction until the Sm2O3 in the mixture is completely reduced to obtain material B;

[0081] (2) Material B was crushed, and then heated to 620° C. (crystallization temperature) under argon protection, and kept warm for 4 hours for crystallization treatment; then the temperature was lowered to 480° C., the argon was evacuated and ammonia was filled in for nitridation treatment for 5 hours, and then cooled to room temperature to obtain nitride, and the nitridation product was placed in deionized water, stirred and washed to wash away the CaO product generated during the Ca reduction process. In order to completely remove CaO, a small amount of hydrochloric acid or acetic acid can also be added to the solution, and then deionized water is used to wash 1-2 times, and the washed product is further washed with alcohol, and the alcohol is filtered and vacuum dried at 60° C., and a nitrogen-oxygen mixed gas with an oxygen content of 0.5% is passed through the powder for 60 hours at room temperature to obtain the magnetic nanoparticles. The nitrogen content analysis shows that the formed compound Sm α Fe γ TM β N ε In, ε=2.95, (γ+β) / α=8.10, ε / α=1.4. .

[0082] Performance Test:

[0083] The particle sizes of the magnetic particles obtained in the test examples and comparative examples were observed by XRD and TEM, and the saturation magnetization Ms and intrinsic coercivity Hcj of the particles were analyzed by VSM. The test results are shown in Table 1:

[0084] Table 1

[0085] Magnetic powder particle size (nm) Ms(emu / g) Hcj(kOe) Example 1 35 151.5 28.1 Example 2 40 155.3 25.3 Example 3 37 150.3 27.3 Example 4 33 122.1 31.5 Example 5 35 145.3 20.1 Example 6 55 140.6 23.7 Example 7 48 149.5 26.6 Example 8 47 143.1 25.8 Example 9 45 139.8 27.4 Comparative Example 1 2350 123.9 8.3

[0086] It can be seen from Table 1 that according to Examples 1-3, the magnetic powder particle size of the magnetic nanoparticles of the present invention can reach below 40 nm, while Ms can reach above 151.5 emu / g, and Hcj can reach above 25.3 kOe.

[0087] By comparing Example 1 with Examples 4-5, it can be seen that the chemical formula of the magnetic nanoparticles of the present invention is Sm α Fe γ TM β N ε In the calculation, α, γ, β and ε need to satisfy the following relationship: 5≤(γ+β) / α≤8.5; 0.05≤β≤0.5. If the range is exceeded, the Ms and Hcj of the material will decrease significantly.

[0088] By comparing Example 1 with Example 6-7, it can be seen that the composition of material A is very critical in the preparation process of the magnetic nanoparticles of the present invention. The present invention designs the composition and content of material A so that it plays the role of fluxing, viscosity reduction, isolation of the main phase (control of particle growth) and collapse in each step, thereby creating organizational conditions for the formation of nanoparticles. The proportion of H3BO3, CaCl2, NaCl, and KCl is controlled at H3BO3 40-75%, CaCl2 15-20%, NaCl 5-20%, and KCl 5-20%, and the performance of the magnetic nanoparticles is better. If it exceeds this range, the grain size of the material increases significantly, and Ms and Hcj decrease significantly.

[0089] By comparing Example 1 with Examples 8-9, it can be seen that in the preparation process of the magnetic nanoparticles of the present invention, the roughness of the roller used will affect the performance of the obtained magnetic nanoparticles. If the surface roughness of the roller is less than 0.05 μm, the surface is too smooth, and the liquid is not easy to spread quickly on the surface of the roller, resulting in the formation of a sheet medium that is too thick, and the medium is not easy to amorphize on the side away from the roller surface; if the surface roughness is greater than 0.20 μm, it is easy to cause the material to stick to the roller, which also reduces the amorphization effect. The reduction in the amorphization effect leads to a significant increase in the grain size of the material, and a significant decrease in Ms and Hcj.

[0090] From the comparison between Example 1 and Comparative Example 1, it can be seen that it is difficult to prepare magnetic nanoparticles by conventional technology, and the Ms and Hcj of the material are significantly lower than those in the example.

[0091] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A magnetic nanoparticle, characterized in that: The chemical formula of the magnetic nanoparticles is Sm α Fe γ TM β N ε , wherein TM includes titanium element, 2≤α≤4, 16.5≤γ≤17.5, 0.05≤β≤0.5, 3.1≤ε≤3.5, and the particle size of the magnetic nanoparticles is 20 to 50 nm.

2. The magnetic nanoparticles according to claim 1, characterized in that The TM further comprises any one of cobalt, vanadium, chromium, manganese or nickel, or a combination of at least two of them.

3. The magnetic nanoparticles according to claim 1 or 2, characterized in that: α, γ, β and ε satisfy the following relationship: 5≤(γ+β) / α≤8.5; 1.35≤ε / α≤1.

8.

4. A method for preparing magnetic nanoparticles according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) H3BO3, CaCl2, NaCl and KCl are mixed to obtain material A, Sm2O3, iron oxide and TM oxide are mixed, ground and then reduced to obtain material B; (2) mixing material A and material B and then melting them to obtain a molten liquid, and flowing the molten liquid onto a rotating cold roller to obtain a flaky amorphous medium; (3) The flaky amorphous medium is crushed and then crystallized, and then nitrided to obtain nitride, which is then washed and passivated to obtain the magnetic nanoparticles.

5. The preparation method according to claim 4, characterized in that: Taking the mass of the material A as 100%, the mass fraction of the H3BO3 is 40-75%; Preferably, based on the mass of the material A being 100%, the mass fraction of the CaCl2 is 15-20%; Preferably, based on the mass of the material A being 100%, the mass fraction of the NaCl is 5 to 20%; Preferably, based on the mass of the material A being 100%, the mass fraction of KCl is 5-20%.

6. The preparation method according to claim 4 or 5, characterized in that: The grinding in step (1) comprises ball milling; Preferably, the reduction treatment includes hydrogen reduction and calcium reduction; Preferably, the temperature of the hydrogen reduction is 800-900°C; Preferably, the temperature of calcium reduction is 950-1050°C.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The mass ratio of material A to material B in step (2) is (20-50):(50-80); Preferably, the temperature of the melt treatment is 1300-1500°C; Preferably, the outflow speed is 4 to 6 g / s; Preferably, the rotating cold roller is made of copper alloy and / or molybdenum alloy; Preferably, the rotation speed of the rotating cold roller is 20-30 m / s; Preferably, the roughness of the rotating cold roller is 0.05-0.2 μm.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The atmosphere of the crystallization treatment in step (3) includes argon; Preferably, the temperature of the crystallization treatment is 580-620°C; Preferably, the crystallization treatment time is 4 to 6 hours; Preferably, the atmosphere of the nitridation treatment comprises ammonia; Preferably, the temperature of the nitriding treatment is 430-480°C; Preferably, the nitriding treatment time is 5 to 7 hours.

9. The preparation method according to any one of claims 4 to 7, characterized in that: The washing treatment in step (3) includes water washing, acid washing and alcohol washing; Preferably, the washing is followed by drying; Preferably, the atmosphere of the passivation treatment comprises a nitrogen-oxygen mixed gas with an oxygen content of 0.5%; Preferably, the passivation treatment time is 40 to 60 hours.

10. A magnetic component, characterized in that: The magnetic component comprises the magnetic nanoparticles according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Sm-Fe-N alloy powder and process for the production thereof

    CN100513015C

  • Rare earth-iron-nitrogen magnet alloy

    CN1093311C